S-Equol Protects Chondrocytes against Sodium Nitroprusside-Caused Matrix Loss and Apoptosis through Activating PI(3)K/Akt Pathway - Huang, Li-Wen (Int J Mol Sci, 2021)
Osteoarthritis (OA) is a common chronic disease with increasing prevalence in societies with more aging populations, therefore, it is causing more concern. S-Equol, a kind of isoflavones, was reported to be bioavailable and beneficial to humans in many aspects, such as improving menopausal symptoms, osteoporosis and prevention of cardiovascular disease. This study investigated the effects of S-Equol on OA progress in which rat primary chondrocytes were treated with sodium nitroprusside (SNP) to mimic OA progress with or without the co-addition of S-Equol for the evaluation of S-Equol’s efficacy on OA. Results showed treatment of 0.8 mM SNP caused cell death, and increased oxidative stress (NO and H(2)O(2)), apoptosis, and proteoglycan loss. Furthermore, the expressions of MMPs of MMP-2, MMP-3, MMP-9, and MMP-13 and p53 were increased. The addition of 30 μM S-Equol could lessen those caused by SNP. Moreover, S-Equol activates the PI(3)K/Akt pathway, which is an upstream regulation of p53 and NO production and is associated with apoptosis and matrix degradation. As a pretreatment of phosphoinositide (3)-kinases (PI(3)K) inhibitor, all S-Equol protective functions against SNP decrease or disappear. In conclusion, through PI(3)K/Akt activation, S-Equol can protect chondrocytes against SNP-induced matrix degradation and apoptosis, which are commonly found in OA, suggesting S-Equol is a potential for OA prevention.